How admissions to various medical specialty divisions determines the outcome of patients with hepatocellular carcinoma: results from a retrospective study in a large hospital of northwest China - Zhu Q; Li N; Li F; Zhou Z; Sang J; Zeng X; Han Q; Lv Y; Zhao W; Liu Z (Dove Medical Press, 2017)
Qianqian Zhu,1 Na Li,1 Fang Li,1 Zhihua Zhou,1 Jiao Sang,1 Xiaoyan Zeng,2 Qunying Han,1 Yi Lv,3,4 Wenxuan Zhao,1 Zhengwen Liu1,4 1Department of Infectious Diseases, 2Department of Laboratory Medicine, 3Department of Hepatobiliary Surgery, The First Affiliated Hospital of Xi’an Jiaotong University, 4Institute of Advanced Surgical Technology and Engineering, Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China Background and objective: The treatment of hepatocellular carcinoma (HCC) involves multidisciplinary clinical divisions and patients may be admitted to clinical divisions of different disciplinary nature. Few studies have assessed the potential effect of hospital admissions into different divisions on patient treatment options and survival. This study aimed to analyze this potential effect. Methods: We analyzed data of HCC patients between 2002 and 2011 in a large hospital of northwest China and compared the treatment options and patient outcomes following initial admission into two major clinical disciplinary divisions: internal medicine and surgical. Barcelona Clinic Liver Cancer criteria were used for staging. Results: The study included 2,045 patients. Analysis showed that more patients initially admitted to surgical divisions received curative treatments (resection, transplantation, and local ablation) than those admitted to internal medicine divisions; while more patients initially hospitalized to internal medicine divisions chose supportive care than those admitted to surgical divisions. Stages 0, A, and B patients initially admitted to surgical divisions had higher survival rates compared with those initially admitted to internal medicine divisions (P=0.036, 0.057 and 0.001, respectively). Survival rates of patients who were in stages C and D showed no differences. The survival differences between patients initially admitted to internal medicine and surgical divisions vanished after adjusting for treatment distribution. Conclusion: This study showed that the initial hospitalization divisions may affect the outcome of HCC patients because of different treatment options, suggesting that enforcing multidisciplinary collaboration to optimize the treatment of HCC patients at various stages may improve patient survival. Keywords: hepatocellular carcinoma, treatment option, outcome, multidisciplinary cooperation